The Experimenting Organization: Using The Results of Behavioral Science Research - Waters, James A.; Salipante, Paul F.; Notz, William W. (Academy of Management Review, 1978)
James A. Waters, Paul F. Salipante, Jr., William W. Notz, The Experimenting Organization: Using the Results of Behavioral Science Research, The Academy of Management Review, Vol. 3, No. 3 (Jul., 1978), pp. 483-492